The Relationship Between Age and The Incidence of Post Dural Puncture Headache in Post Sectio Caesarea Patients with Spinal Anesthesia - Khofifah; Lintang Suryani, Roro; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2024)
Background: Caesarean Section (CS) is a surgical procedure involving incisions in the abdominal wall and uterus. Spinal anesthesia is the preferred method due to the lower maternal morbidity and mortality risks compared to general anesthesia. However, the most common complication associated with spinal anesthesia is Post Dural Puncture Headache (PDPH), caused by a dural puncture. Age is a significant factor influencing PDPH occurrence. Patients aged 20-40 are at a higher risk, while those over 50 years have a reduced risk due to the decrease in cranial elasticity and pain sensitivity with age. Purpose: This study aims to assess the correlation between age and the incidence of PDPH following spinal anesthesia in CS patients. Methods: This study employed a cross-sectional analytic correlation design. The sample included all CS patients who received spinal anesthesia and met the study criteria, totaling 35 respondents. Data were analyzed using univariate and bivariate analysis, with the correlation significance tested at 0.05 (2-tailed). Findings: The study revealed that 14.3% of respondents experienced PDPH, while 85.7% did not. A significant correlation was found between age and PDPH incidence, with a p-value of 0.05. The highest incidence of PDPH was observed in the 20-40 age group, decreasing notably in individuals aged 50 and above. Conclusion: This study highlights that PDPH risk is highest in patients aged 20-40 and significantly decreases in patients older than 50. Age-related changes in cranial structure and pain sensitivity likely contribute to this decreased risk.